Short Androgen Suppression and Radiation Dose Escalation in Prostate Cancer: 12-Year Results of EORTC Trial 22991 in Patients With Localized Intermediate-Risk Disease. Issue 27 (20th September 2021) - Bolla, Michel; Neven, Anouk; Maingon, Philippe; Carrie, Christian; Boladeras, Ana; Andreopoulos, Demetrios; Engelen, Antoine; Sundar, Santhanam; van der Steen-Banasik, Elzbieta M.; Armstrong, John; Peignaux-Casasnovas, Karine; Boustani, Jihane; et al.
Abstract : PURPOSE: The European Organisation for Research and Treatment of Cancer (EORTC) trial 22991 (NCT00021450 ) showed that 6 months of concomitant and adjuvant androgen suppression (AS) improves event- (EFS, Phoenix) and clinical disease-free survival (DFS) of intermediate- and high-risk localized prostatic carcinoma, treated by external-beam radiotherapy (EBRT) at 70-78 Gy. We report the long-term results in intermediate-risk patients treated with 74 or 78 Gy EBRT, as per current guidelines. PATIENT AND METHODS: Of 819 patients randomly assigned between EBRT or EBRT plus AS started on day 1 of EBRT, 481 entered with intermediate risk (International Union Against Cancer TNM 1997 cT1b-c or T2a with prostate-specific antigen (PSA) ≥ 10 ng/mL or Gleason ≤ 7 and PSA ≤ 20 ng/mL, N0M0) and had EBRT planned at 74 (342 patients, 71.1%) or 78 Gy (139 patients, 28.9%). We report the trial primary end point EFS, DFS, distant metastasis–free survival (DMFS), and overall survival (OS) by intention-to-treat stratified by EBRT dose at two-sided α = 5%. RESULTS: At a median follow-up of 12.2 years, 92 of 245 patients and 132 of 236 had EFS events in the EBRT plus AS and EBRT arm, respectively, mostly PSA relapse (48.7%) or death (45.1%). EBRT plus AS improved EFS and DFS (hazard ratio [HR] = 0.53; CI, 0.41 to 0.70; P < .001 and HR = 0.67; CI, 0.49 to 0.90; P = .008). At 10 years, DMFS was 79.3% (CI, 73.4 to 84.0) with EBRT plus AS and 72.7% (CI, 66.2 to 78.2) with EBRT (HR = 0.74; CI, 0.53 to 1.02; P = .065). With 140 deaths (EBRT plus AS: 64; EBRT: 76), 10-year OS was 80.0% (CI, 74.1 to 84.7) with EBRT plus AS and 74.3% (CI, 67.8 to 79.7) with EBRT, but not statistically significantly different (HR = 0.74; CI, 0.53 to 1.04; P = .082). CONCLUSION: Six months of concomitant and adjuvant AS statistically significantly improves EFS and DFS in intermediate-risk prostatic carcinoma, treated by irradiation at 74 or 78 Gy. The effects on OS and DMFS did not reach statistical significance.